A host target of a bacterial cysteine protease virulence effector plays a key role in convergent evolution of plant innate immune system receptors. Issue 3 (31st October 2019) - Prokchorchik, Maxim; Choi, Sera; Chung, Eui‐Hwan; Won, Kyungho; Dangl, Jeffery L.; Sohn, Kee Hoon
Summary: Some virulence effectors secreted from pathogens target host proteins and induce biochemical modifications that are monitored by nucleotide‐binding and leucine‐rich repeat (NLR) immune receptors. Arabidopsis RIN4 protein (AtRIN4: RPM1‐interacting protein 4) homologs are present in diverse plant species and targeted by several bacterial type III effector proteins including the cysteine protease AvrRpt2. RIN4 is 'guarded' by several independently evolved NLRs from various plant species, including Arabidopsis RPS2. Recently, it was shown that the MR5 NLR from a wild apple relative can recognize the AvrRpt2 effector from Erwinia amylovora, but the details of this recognition remained unclear. The present contribution reports the mechanism of AvrRpt2 recognition by independently evolved NLRs, MR5 from apple and RPS2, both of which require proteolytically processed RIN4 for activation. It shows that the C‐terminal cleaved product of apple RIN4 (MdRIN4) but not AtRIN4 is necessary and sufficient for MR5 activation. Additionally, two polymorphic residues in AtRIN4 and MdRIN4 are identified that are crucial in the regulation of and physical association with NLRs. It is proposed that polymorphisms in RIN4 from distantly related plant species allow it to remain an effector target while maintaining compatibility with multiple NLRs.